In-Stent Ulceration: An Unusual Pathology - Jagadeesh Kumar Kalavakunta; Shravan Gangula; Vishal Gupta (Case Reports in Cardiology)
In-stent restenosis occurs in 10–60% of cases undergoing interventional therapy. Many mechanisms explain the reason for in-stent restenosis, but restenosis due to an ulcerated plaque is very rare and has not been well reported in the literature. We report an interesting case of 72-year-old man presenting with neurological symptoms secondary to in-stent restenosis of the carotid artery caused by an ulcerated plaque. We also explain the different mechanisms for restenosis along with the treatment options.